PENGARUH KOMPENSASI, LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. FINANSIA MULTI FINANCE CABANG BATAM - Desty Sri Wulandari,; Rona Tanjung, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2020)
The purpose of this study to determine the effect of compensation, work environment and organizational culture on employee job satisfaction at PT. Finansia Multi Finance Batam Branch. This research uses quantitative method. the Population of this study were 150 employees who worked at PT. Finansia Multi Finance Batam Branch. The research sample was 60 employees, the analysis technique used multiple linear regression. Based on T-test known compensation has a positive and significant effect on employee job satisfaction with tcount,(5,685) > ttable (1,672) and significant value 0,000 < 0,05, the work environment has a positive and significant effect on employee job satisfaction with tcount,(3,658) > ttable (1,672) and significant value 0,001 < 0,05, and organizational culture has a negative and significant effect on employee job satisfaction with tcount,(-3,479) < ttable (1,672) and significant value 0,001 < 0,05. Based on the F-test known compensation, work environment and organizational culture also have a positive and significant effect on job satisfaction of employee at PT. Finansia Multi Finance Batam Branch with fcount (24,388) > ftable (2,77) and significant value 0,000 < 0,05